THE INFLUENCE OF PARENTAL EDUCATION LEVEL, SOCIO-ECONOMIC STATUS, AND LEARNING MOTIVATION ON THE ACADEMIC PERFORMANCE OF HIGH SCHOOL STUDENTS AT SEKOLAH INDONESIA DAVAO, PHILIPPINES - Almira, Fatihah Nara; Wibowo, Agus; Zahra, Siti Fatimah (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
Education is a process that continuously transfers knowledge, skills, values, and attitudes to develop intellectual abilities and prepare individuals for societal roles. Learning outcomes are influenced by factors such as parental education levels, socioeconomic status, and learning motivation. This study examines the relationship between these factors and academic performance among high school students at Sekolah Indonesia Davao (SID) in Davao City, Philippines. Conducted from February to May 2024, the research involved 39 students using a 1-5 Likert scale questionnaire via Google Forms, and multiple linear regression analysis was employed to assess the impact of the independent variables on academic performance. The results indicated that the overall model was not significant (p-value = 0.5530), meaning the independent variables did not significantly explain the variance in academic performance. Individual analysis of Parental Education Level, Socioeconomic Status, and Learning Motivation also showed non-significant results, with all p-values ​​exceeding 0.05. The fit statistics supported these findings, with an R² value of 0.0573 indicating very weak explanatory power, and negative adjusted R² (-0.0235) and predicted R² (-0.1820) values ​​highlighting the model's poor performance. The study concludes that these factors do not significantly impact the academic performance of SID students, suggesting the need for further research to identify other variables that might better explain the variability in academic performance among high school students at SID.